Social mobility perceptions and inequality acceptance - Fehr, Dietmar; Müller, Daniel; Preuß, Marcel (Working papers in economics and statistics, 2020)
This paper examines how perceptions of social mobility affect acceptance of inequality. We conduct a randomized information intervention in a large and heterogeneous sample of Germans to manipulate beliefs about social mobility. While the information treatment renders social mobility perceptions significantly more pessimistic, we find strong evidence that these more pessimistic perceptions change neither revealed distributional preferences nor support for greater redistribution or education spending. We present suggestive evidence for the lack of a measurable treatment effect. Participants do not seem to perceive low mobility rates as unfair, as they do not link the persistence of socioeconomic status to luck. Finally, the large sample size allows us to rule out economically meaningful treatment effects.
Keywords: Graue Literatur